Measurement of the B0 production cross section in pp collisions at sqrt[s] = 7 TeV. - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2011)
Measurements of the differential production cross sections dσ/dpTB and dσ/dyB for B0 mesons produced in pp collisions at sqrt[s] = 7 TeV are presented. The data set used was collected by the CMS experiment at the LHC and corresponds to an integrated luminosity of 40 pb-1. The production cross section is measured from B0 meson decays reconstructed in the exclusive final state J/ψKS0, with the subsequent decays J/ψ → μ + μ - and KS0 → π+}π-. The total cross section for pTB>5 GeV and |yB|<2.2 is measured to be 33.2 ± 2.5 ± 3.5 μb, where the first uncertainty is statistical and the second is systematic.